TBK1 mutations in Italian patients with amyotrophic lateral sclerosis: genetic and functional characterisation. Issue 10 (19th August 2017) - Pozzi, Laura; Valenza, Fabiola; Mosca, Lorena; Dal Mas, Andrea; Domi, Teuta; Romano, Alessandro; Tarlarini, Claudia; Falzone, Yuri Matteo; Tremolizzo, Lucio; Sorarù, Gianni; Cerri, Federica; Ferraro, Pilar M; et al.
Abstract : Background: TANK-binding kinase 1 ( TBK1 ) gene has been recently identified as a causative gene of amyotrophic lateral sclerosis (ALS). Methods: We sequenced the TBK1 gene in a cohort of 154 Italian patients with ALS with unclear genetic aetiology. We subsequently assessed the pathogenic potential of novel identified TBK1 variants using functional in vitro studies: expression, targeting and activity were evaluated in patient-derived fibroblasts and in cells transfected with mutated- TBK1 plasmids. Results: We identified novel genomic TBK1 variants including two loss-of-function (LoF) (p.Leu59Phefs*16 and c.358+5G>A), two missense (p.Asp118Asn and p.Ile397Thr) and one intronic variant (c.1644–5_1644-2delAATA), in addition to two previously reported pathogenetic missense variants (p.Lys291Glu and p.Arg357Gln). Functional studies in patient-derived fibroblasts revealed that the c.358+5G>A causes aberrant pre-mRNA processing leading TBK1 haploinsufficiency. Biochemical studies in cellular models showed that the truncating variant p.Leu59Phefs*16 abolishes TBK1 protein expression, whereas the p.Asp118Asn variant severely impairs TBK1 phosphorylation activity. Conversely, the p.Ile397Thr variant displayed enhanced phosphorylation activity, whose biological relevance is not clear. Conclusion: The observed frequency of TBK1 LoF variants was 1.3% (2/154), increasing up to 3.2% (5/154) by taking into account also the functional missense variants that we were able to classify as potentially pathogenic, supporting the relevance of TBK1 in the Italian population with ALS.